Neutrophil-Mediated Effects on Hemostasis and Thrombosis: Unraveling Their Complex Interaction in Thrombotic Events - Hassani, Saeed; Fazeli, Alieh; Dorgalaleh, Akbar; Tabibian, Shadi; Lomei, Jalal; Alipour, Maedeh; Kiani Zadeh, Masoumeh; Shams, Mahmood (Seminars in Thrombosis and Hemostasis, 2025)
Neutrophils are astonishing cells involved in nonspecific immunity, especially against bacterial and fungal infections. Their half-life is short, but despite their important role in nonspecific immunity, they defend the host even after their death by providing secondary structures such as neutrophil extracellular traps (NETs). NETs are a network comprising DNA, histones, and proteins, including elastase, cathepsin G, and myeloperoxidase. In this context, in addition to their primary role in hemostasis, they also play a role in thrombosis, an area that has received less attention. Nonetheless, NETs can promote both venous and arterial thrombus formation (immuno-thrombosis), by their effects on primary and secondary hemostasis; their participation in thrombus formation includes the release of microparticles and components of the inflammasome. Neutrophils in interaction with other cells including platelets can further contribute to thrombosis. Activated platelets can capture neutrophil-derived microparticles containing tissue factor (TF), leading to TF accumulation and increased fibrin deposition. Furthermore, neutrophil inflammasomes as a regulator of the generation of IL-1 family proteins have been shown to augment thrombosis formation in response to hypoxia. Overall, understanding the complex and reciprocal effects of neutrophils with other hemostasis-related cells and components provides important insights into hemostatic mechanisms, and this may open avenues in medical research and potential therapeutic interventions.
Keywords: neutrophil; thrombosis; hemostasis; fibrinolysis; neutrophil extracellular traps